ผลของการอบแห้งด้วยเทคนิคฟลูอิไดเซชันร่วมกับเทมเปอริง และอุณหภูมิในการเก็บต่อปริมาณ 2AP และคุณภาพการสีของข้าวขาวดอกมะลิ 105 Oryza sativa L. - รริศรา อิ่มภาประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objective of this research is to study the effects of high temperature drying by using fludization technique with tempering as well as and storage temperatures on aroma and milling quality of Khao Dawk Mali 105 (Oryza sative L.). The experiment was divided into 3 parts; in the first part the suitable time to reduce moisture content of paddy to required level for first and second fluidized bed drying was determined. The second part, the changes of milling quality: head rice yield (HRY), white index (WI) and aroma quality: 2-Acetyl-1-pyrroline (2AP) content after subjected to drying was studied. In the final experiment, dried paddy was stored under different conditions and the changes of milling and aroma quality were observed during storage for 6 months. The results showed that the first stage of drying by temperature fluidization required 3, 3, 2.5 and 2 minutes to reduce moisture content of the paddy from 35-37%db to 23-24 % db, while the second fluidization after tempering required 3, 2, 1.5 and 1 minutes to reduce moisture content from 23-24% db to 15-17% db for drying temperature of 115, 125, 135 and 150 ํ C respectively. After drying, it was found that drying temperatures had effects on HRY, white index and 2AP content. The relative white index was found to be higher than 80% but it was still in the commercial limit. Furthermore, most of the drying temperature gave the low level of HRY except for 150ํC which had significant increasing of head rice yied (p is less than or equal to 0.05). However, when replaced the second fluidization with shade drying after the first fluidization and tempering, HRY increased significantly especially at 135 and 150ํC (p is less than or equal to .05). During storage, the moisture content was subjected to the change of ambient relative humidity. 2AP content decreased significantly (p is less than or equal to 0.05) while HRY and white index were not changed. When compare between ambient temperature (28-30ํC) and 15ํC storage condition, it was found that the suitable condition to maintain 2 AP content was 15ํC. However, the storage condition dose not significantly affect the HRY and white index of rice (p>0.05).